Willingness to pay for recycled aggregates in concrete among German construction clients - Ellen Sterk (Philipps-University Marburg, School of Business and Economics, 2023)
The construction industry claims a vast quantity of natural resources and is responsible for more than half of the waste generated in Germany. R-concrete contains recycled aggregates and is a resource efficient alternative to primary concrete. A central stakeholder whose preferences may significantly influence the use of R-concrete is the construction client. Despite their central role in this respect, little is known about clients. This study contributes to the understanding of the clients' demand decision. It determines the willingness to pay (WTP) for recycled aggregates and it examines which factors influence clients' propensity to choose R-concrete. Additionally, the study identifies barriers and drivers for the demand for R-concrete. Throughout these questions, differences between client groups are considered. In addition to item-based questions on potential barriers and drivers, a discrete choice experiment is applied to estimate the clients' WTP for a certain share of recycled aggregates in concrete. Positive and significant WTP estimates were found for all client groups. Overall, clients are willing to pay 0.26 exteuro for every percentage point increase of added recycled aggregates. Private individuals' WTP is lowest, while organizations are willing to pay most. However, even organizations' WTP does not equal the price premium currently seen. The main barriers for demanding R-concrete are based on a lack of information. Therefore, in order to foster the use of R-concrete, instruments that rely on information provision are recommended. Moreover, the significant differences in client groups should be considered in designing these instruments
Keywords: 330; Bauwirtschaft; Baustoff; Beton; Betriebliche Kreislaufwirtschaft; Zahlungsbereitschaftsanalyse; Deutschland